Understanding the role of grievance and fixation in lone actor violence - Brooks, Nathan; Barry-Walsh, Justin (Frontiers in Psychology, 2022)
In pursuit of public discourse, there is a risk of a simple polarity in thinking, meaning acts of public/mass violence, or those where there is a risk of public violence are categorised as terrorist acts or not. The reliance on categorisation, and the pursuit of assigning ideology, diminishes the complexity of factors contributing to these forms of offending. This approach misses a critical opportunity to understand the pathways to violence and reduces the significance of comorbid or co-occurring factors that give rise to the violence. Lone Actor Grievance Fuelled Violence (LAGFV) is a recently utilised term based on mounting evidence that those who seek to perpetrate acts of lone actor violence, whether this be those where a terrorist motivation can be assigned, a school attacks, workplace attack, or an attack in a public place, are commonly fuelled by grievance and fixation. LAGFV at this juncture is a blurry construct without definitive rules and boundaries, and instead provides a guiding conceptualisation of a diverse group of offenders who commit targeted violence towards others. The current review contends that LAGFV emerges through the perceived thwarting of psychological needs and the central task for clinicians and other professional services lies in understanding the unique pathways and contributing factors that give rise to violence for each specific individual/case. The review contends that is not fit to determine whether an act is of ideological significance, or constituting terrorism, without understanding the psychosocial and circumstantial factors contributing to the violence.